The role of anti-neutrophil cytoplasmic autoantibody specificity for mpo or pr3 in phenotype of anca associated vasculitis: knowing the autoimmunity in latin america (2018)
ABSTRACT: Background: Antineutrophil cytoplasmic antibodies (ANCA) are present in up to 90% granulomatosis with polyangiitis, 80% microscopic polyangiitis and 70% eosinophilic granulomatosis with polyangiitis. MPO-ANCA has been associated with vasculitis limited to the kidney, chronic renal damage and less frequent gastrointestinal or respiratory tract involvement. PR3-ANCA are characterised by destructive lesions of the ears, nose and throat, alveolar haemorrhage, combination of upper and/or lower respiratory tract involvement with renal compromise and increased number of relapses. The frequency of pulmonary involvement is similar in both serotypes, and most ANCA associated vasculitis (AAV) patients are diagnosed between ages 50 and 70 years. Objectives: To describe differences in clinical profiles of patients with AAV regarding ANCA specificity against MPO or PR3 in a Colombian based adult population Methods: All medical records of patients with a diagnosis of AAV in two high complexity hospitals in Medellín, Colombia from January 1, 2014 to December 31, 2016 were reviewed. The clinical and demographic characteristics were abstracted and analysed with descriptive and inferential statistics in SPSS.22 Results: Of 59 cases of AAV, 44 were positive for MPO or PR3-ANCA with male predominance (65.5% men vs 34.5% women) and similar age at diagnosis (47 years in MPO-ANCA vs 50 in PR3-ANCA). MPO-ANCA group had more fever and weight loss (34.8% vs 20%), arterial hypertension (34.5% vs 26.7%), hematuria (34.5% vs 26.7%), proteinuria (31% vs 26.7%), creatinin higher than 5.6 mg/dL (20.7 vs 13.3%), myalgias (13.8 vs 0%) pachymeningitis (7% vs 0%) and skin compromise. PR3-ANCA patients had more arthralgias/arthritis (40% vs 31%), escleritis (33% vs 13.8%), episcleritis (13.3% vs 0%) and uveítis (10% vs 7%). Conclusions: In this Latin American population ANCA specificity affected the phenotype of clinical disease. MPO-ANCA patients had more constitutional symptoms, renal and central nervous system compromise while PR3-ANCA patients showed more articular and ocular involvement.